Efficacy and safety of Tanreqing Injection combined with conventional antimicrobial therapy in the treatment of multidrug-resistant bacterial pneumonia: a meta-analysis - Shu, Bofei; Qiu, Tingting; Li, Keke; Wang, Xiaolin; Fang, Bangjiang (The Journal of Infection in Developing Countries, 2026)
Background: Multidrug-resistant (MDR) bacterial pneumonia is a growing public health concern with limited treatment options and high mortality rates. Tanreqing injection, a traditional Chinese medicine with anti-inflammatory, antibacterial, and immunomodulatory properties, has shown potential as an adjunctive therapy, but its efficacy and safety remain unclear. Methods: A systematic search of six English and Chinese databases was conducted to identify randomized controlled trials (RCTs) published before July 2025 evaluating Tanreqing injection for MDR pneumonia. Meta-analysis was performed using RevMan 5.4. Primary outcomes included clinical effectiveness and 28-day all-cause mortality. Secondary outcomes included bacterial clearance, inflammatory markers (WBC, CRP, PCT), healthcare utilization (duration of antibiotic use, mechanical ventilation, hospital stay), and adverse events. Risk of bias was assessed using the RoB 2.0 tool. Results: Seventeen RCTs involving 1,616 patients were included. All studies were conducted in China. Tanreqing combined with standard therapy significantly improved clinical effectiveness (RR = 1.21) and bacterial clearance (RR = 1.42), and reduced CRP, WBC, PCT, antibiotic duration (MD = -3.55 days), ventilation time (MD = -1.57 days), and hospital stay (MD = -4.98 days). A trend toward lower 28-day mortality was observed (RR = 0.56, p = 0.15). No serious adverse events were reported. Publication bias was not significant (Harbord test, p = 0.639). Conclusions: Tanreqing injection may enhance the clinical outcomes of patients with MDR pneumonia when used alongside antibiotics and appears to be safe and well-tolerated. Further high-quality RCTs are needed to confirm these findings.